Design of multi-tier multi-time horizon closed-loop supply chain network with sustainability under uncertain environment for Indian paper industry - Kamlesh Pant; Vinay Surendra Yadav; A. R. Singh (International Journal of Sustainable Engineering, 2021)
Due to increased awareness and strictly imposed legislations, Supply Chain (SC) managers are often forced to include recovery system in their SC. Recovery systems make use of 3 Rs, namely, recycling, reuse and remanufacturing which results in the transformation of traditional SC into closed-loop supply chain (CLSC). Recovery of discarded product in such forms is an effective way to deal with afterlife of product, leading to sustainable development. In this work, a bi-objective CLSC model has been developed for the paper industry under uncertain environment. The first objective of the proposed model is to maximise SC surplus, and the second objective is to incorporate sustainability through minimising carbon content by reducing the number of trucks between various echelons of CLSC network. In the proposed model, sustainability has been considered by two means: first to reduce the demand of next period by refurbishing some of the product collected from the customers and second is to reduce the raw material requirement at vendor side by using some of the recycled and usable product from the recycling centre. Further, various numerical illustrations are being performed and results are interpreted for a case paper industry which validates the application of the proposed model.